2018
DOI: 10.1088/1361-6463/aad524
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale understanding of the permeation of plasma species across native and oxidized membranes

Abstract: Cold atmospheric plasmas (CAPs) have attracted significant interest for their potential benefits in medical applications, including cancer therapy. The therapeutic effects of CAPs are related to reactive oxygen and nitrogen species (ROS and RNS) present in the plasma. The impact of ROS has been extensively studied, but the role of RNS in CAP-treatment remains poorly understood at the molecular level. Here, we investigate the permeation of RNS and ROS across native and oxidized phospholipid bilayers (PLBs) by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 60 publications
6
41
0
Order By: Relevance
“…If the intracellular oxidative stress triggered by free radicals exceeds the amount that can be handled by the anti-oxidative defense system apoptosis will be induced through a signaling cascade [31]. By means of computer simulations, the permeation of ROS and RNS across native and oxidized phospholipid bilayers has been investigated and these analyses revealed that the assessed RNS (i.e., NO, NO 2 , N2O 4 ) and O 3 can permeate more easily through both native and oxidized phospholipid bilayers compared to hydrophilic ROS (i.e., OH, HO 2 , H 2 O 2 ), indicating their potential importance in plasma medicine [32]. Nitric oxide (NO) regulates posttranslational modifications, S-nitrosation, as well as genome-wide epigenetic modifications that can have both tumor-promoting and tumor-suppressing effects [33].…”
Section: Selectivity Of Cap Towards Malignant Cellsmentioning
confidence: 99%
“…If the intracellular oxidative stress triggered by free radicals exceeds the amount that can be handled by the anti-oxidative defense system apoptosis will be induced through a signaling cascade [31]. By means of computer simulations, the permeation of ROS and RNS across native and oxidized phospholipid bilayers has been investigated and these analyses revealed that the assessed RNS (i.e., NO, NO 2 , N2O 4 ) and O 3 can permeate more easily through both native and oxidized phospholipid bilayers compared to hydrophilic ROS (i.e., OH, HO 2 , H 2 O 2 ), indicating their potential importance in plasma medicine [32]. Nitric oxide (NO) regulates posttranslational modifications, S-nitrosation, as well as genome-wide epigenetic modifications that can have both tumor-promoting and tumor-suppressing effects [33].…”
Section: Selectivity Of Cap Towards Malignant Cellsmentioning
confidence: 99%
“…We performed MD simulations to study the permeation of H 2 O 2 across lipid bilayers with various compositions. Although CAPs generate many different RONS, we choose to focus on H 2 O 2 as (i) we demonstrated in our previous work [34,35] that all polar RONS behave in the same way as H 2 O 2 , and (ii) as the vesicles are treated in a liquid solution, so a large fraction of the short-lived RONS generated by the plasma jet (e.g., • OH) will recombine before reaching the vesicles, making H 2 O 2 the most abundant reactive species present in the solution. As in the experiments, ten different bilayers were constructed, of which the composition was chosen to mimic the composition of the vesicles studied experimentally, i.e., the bilayers contained different concentrations of DPPE and cholesterol in DPPC or DOPC systems.…”
Section: Simulation: H 2 O 2 Delivery Across Different Membrane Compomentioning
confidence: 99%
“…Notably, all these effects can be tumor-promoting or tumor-suppressing in a dose-dependent manner, followed by proliferation, chemoresistance, angiogenesis and metastasis or apoptosis, anti-angiogenesis, and enhanced chemo-sensitivity. Moreover, computer simulations showed that RNS reveal enhanced permeability through phospholipid bilayers compared to that of reactive oxygen species (ROS) [32]. Considering that elevated RONS levels overstrain the antioxidant resistance of cancer cells, MABS promises to be highly effective, as we found the reactivity of MABS significantly higher compared to the kINPen due to greater excitation of atoms measured by spatially resolved OES and higher levels of generated oxygen-centered radicals analyzed by ESR ( Figure 1) [19,21].…”
Section: Discussionmentioning
confidence: 76%